Psychological Status, Compliance, Serum Brain-Derived Neurotrophic Factor, and Nerve Growth Factor Levels of Patients with Depression after Augmented Mindfulness-Based Cognitive Therapy - Huirong Guo; Yuming Ren; Bailing Huang; Junru Wang; Xuhuang Yang; Yali Wang (Genetics Research)
Objective. Mindfulness-based cognitive therapy (MBCT) is a cost-effective psychosocial program that prevents relapse/recurrence in major depression. The present study aimed to analyze the effects of augmented MBCT along with standard treatment dominated by pharmacotherapy on psychological state, compliance, brain-derived neurotrophic factor (BDNF), and nerve growth factor (NGF) expression levels in patients with depression. Methods. A total of 160 eligible patients with depression in The First Affiliated Hospital of Zhengzhou University were included in this study. The study randomly assigned the patients to the experimental group (n = 80) and control group (n = 80). All participants were assessed with the questionnaires including the 17-item Hamilton Depression Rating Scale (HAMD-17), Rosenberg Self-esteem Scale (RSES), Self-Acceptance Questionnaire (SAQ), and Stigma Scale (Scale of Stigma in People with Mental Illness, SSPM). The serum levels of BDNF and NGF were detected by enzyme-linked immunosorbent assay (ELISA). Results. After 8 weeks of treatment, the experimental group showed significant lower HAMD-17 score, higher RSES, and SAQ score, as well as lower SSPM score compared with the control group (P<0.01). Furthermore, ELISA revealed that the serum levels of BDNF and NGF remarkably increased in the experimental group after treatment (P<0.001). Conclusions. Our data showed that augmented MBCT combined with pharmacotherapy contributed to improvement on patients’ psychological state, compliance, and disease recurrence.